Autoimmune B Cell Repertoire in a Mouse Model of Sjögren’s Syndrome - Sáez Moya, Manuel; Gutiérrez-Cózar, Rebeca; Puñet-Ortiz, Joan; Rodríguez de la Concepción, María Luisa; Blanco, Julià; Carrillo, Jorge; Engel, Pablo (Frontiers in Immunology, 2021)
In genetically prone individuals, chronic immune activation may lead to expansion of autoreactive lymphocyte clones that can induce organ damage developing autoimmune disorders. Sjögren’s Syndrome (SjS) is a systemic chronic autoimmune disease that primarily affects exocrine glands. Despite the accumulated evidences of profound B-cell alterations of humoral immunity, the repertoire and development of B-cell autoreactivity in SjS remains to be determined. We hypothesize that SjS mice will have an increased frequency of self-reactive B cells with a progressive evolution to antigen-driven oligoclonality. Here, we study the B cell repertoire of NOD.H-2h4 mice, a mouse model of spontaneous autoimmunity mimicking SjS without developing diabetes. A library of 168 hybridomas from NOD.H-2h4 mice and 186 C57BL/6J splenocytes at different ages was created. The presence of mono or polyreactive autoantibodies to several antigens was evaluated by ELISA, and their staining patterns and cellular reactivity were tested by IFA and FACS. We observed a higher frequency of autoreactivity among B-cell clones from NOD.H-2h4 mice as compared to wild-type mice. The presence of polyreactive and autoreactive IgG clones increased with mice age. Strikingly, all anti-Ro52 autoantibodies were polyreactive. No loss of polyreactivity was observed upon antibody class switching to IgG. There was a progression to oligoclonality in IgG B cells with mice aging. Our results indicate that in the NOD.H-2h4 mouse model of SjS, IgG+ B cells are mainly polyreactive and might expand following an unknown antigen-driven positive selection process.